Judul Dampak Bencana Banjir Rob dan Adaptasi Masyarakat terhadapnya di Kabupaten Semarang - Indahsari, Sheria Arih; Hidayatulloh, Ahmad Fauzan (Jurnal Energi Baru dan Terbarukan, 2023)
Environmental problems are beginning to emerge and change. One of the environmental challenges that many people are concerned about is global warming. An increase in sea level is one of the numerous effects of global warming. Settlements along the seaside are frequently flooded by the tides. Semarang is one of Indonesia's major cities that is situated along the coast and is subject to tidal flooding. The purpose of this study was to ascertain the effects of coastal flooding (rob) in Semarang Regency and the ways in which the local population responded to this catastrophe. Direct observation in Tambak Lorok hamlet in Semarang Regency, as well as analysis of the literature, which was helpful for obtaining theories to support the research.